2010
DOI: 10.1186/ar3120
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes/macrophages express chemokine receptor CCR9 in rheumatoid arthritis and CCL25 stimulates their differentiation

Abstract: IntroductionMonocytes/macrophages accumulate in the rheumatoid (RA) synovium where they play a central role in inflammation and joint destruction. Identification of molecules involved in their accumulation and differentiation is important to inform therapeutic strategies. This study investigated the expression and function of chemokine receptor CCR9 in the peripheral blood (PB) and synovium of RA, non-RA patients and healthy volunteers.MethodsCCR9 expression on PB monocytes/macrophages was analysed by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 51 publications
1
40
2
1
Order By: Relevance
“…CCR9 is the principal chemokine receptor for the thymus expressed chemokine [41]. Some data also suggest that regulated expression of CCR9 is critical for normal development of immature thymocytes and CCR9 on these CD14þ cells may play a role in the differentiation of recently immigrated monocytes [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…CCR9 is the principal chemokine receptor for the thymus expressed chemokine [41]. Some data also suggest that regulated expression of CCR9 is critical for normal development of immature thymocytes and CCR9 on these CD14þ cells may play a role in the differentiation of recently immigrated monocytes [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…CCR9, one of the CC subset chemokine receptors, was initially reported in thymus and small intestine (Vicari et al 1997;Wurbel et al 2000). More recent studies have shown that CCR9 was highly expressed in other tissues besides thymus and intestine, which were involved in many kinds of disease processes, including rheumatoid arthritis, inflammatory bowel disease and hepatitis (Apostolaki et al 2008;Nakamoto et al 2012;Schmutz et al 2010), while the role of CCR9 in acute transplant rejection remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Originally, the CCR9-CCL25 interaction was found to be involved in T cell development in the thymus (Vicari et al 1997) and T-cell homing to the small intestine (Kunkel et al 2000;Wurbel et al 2000). However, accumulating evidences showed that the CCR9/ CCL25 axis participated in a variety of disease processes (Johnson-Holiday et al 2011;Nakamoto et al 2012;Schmutz et al 2010). In Crohn's disease patients (M et al 2007) and in a murine model (Apostolaki et al 2008;Rivera-Nieves et al 2006), CCL25 was up-regulated following accumulation of CCR9…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that expression of CCR9 on macrophages is required for inflammatory response in Con A-induced hepatitis and rheumatoid arthritis [16,17]. To investigate additional roles of CCR9, we examined its expression on peritoneal macrophages.…”
Section: Ccr9 Is Induced On Peritoneal Macrophagesmentioning
confidence: 99%
“…CCL25 is induced in the colon in a murine model of acute colitis, and ameliorates colitis severity by recruiting tolerogenic CCR9 + pDCs [15]. Recently, we and other groups have shown that CCR9 is also expressed on macrophages, and that its expression is required for induction or maintenance of inflammation in Concanavalin A (Con A)-induced hepatitis and human rheumatoid arthritis [16,17]. It is also known that CCR9/CCL25 interaction induces not only chemotaxis, but also activation and development of macrophages [16,17].…”
Section: Introductionmentioning
confidence: 99%